Ability Improvement and Critical Literacy With Science Textbook Literacyof Buffer Solution (Journal of Innovative Science Education, 2017)
The goals of this study is to test the increasing of ability, critical literacy and to describe the ability profile and critical literacy profile of the students using science text book based on scientific literacy buffer solution. The type of this research is a mixed methode with Concurrent Triangulation model. Science text book based on scientific literacy used in this study met the valid criteria with score 3,75. Increased ability with N-gain achievement of 0.79 with high achievement criteria. Based on the one-party t test with Î± = 5% and descriptive analysis, it was found that the improvement of ability and critical literacy using science text book based on scientific literacy is better than using BSE teaching materials. Aspects of science as a body of knowledge has increased 83%, science as way of investigation has increased 74%, science as way of thinking has increased 82%, and interaction of science,, technology, society and environment has increased 81%. Increased critical literacy with N-gain achievement of 0,76 by the criteria of achievement level high. Aspects of reading comprehension have improved 85%, and aspects of using information from reading material have increased 70%. It can be concluded that there is an increase of ability and critical literacy of the students using science text book based on scientific literacy of buffer solution. Tujuan dari penelitian ini adalah menguji peningkatan ability dan critical literacy serta mendeskripsikan profil ability, dan critical literacy siswa menggunakan bahan ajar berbasis literasi sains materi larutan penyangga. Penelitian ini merupakan penelitian mixed method dengan model Concurrent Triangulation. Bahan Ajar berbasis literasi sains yang digunakan pada penelitian ini memenuhi criteria sangat valid dengan perolehan skor 3,75. Peningkatan ability dengan capaian N-gain sebesar 0,79 dengan criteria tingkat pencapaian tinggi. Berdasarkan uji t satu pihak dengan Î± = 5% dan analisis deskriptif, diperoleh bahwa peningkatan ability dan critical literacy menggunakan bahan ajar berbasis literasi sains lebih baik di bandingkan menggunakan bahan ajar BSE. Aspek sains sebagai batang tubuh pengetahuan mengalamipeningkatan83%, sains sebagai penyelidikan hakikat sains mengalami peningkatan 74%, sains sebagai cara berpikir mengalami peningkatan 82%, dan hubungan sains, teknologi, masyarakat dan lingkungan mengalami peningkatan 81%. Peningkatan critical literacy dengan capaian N-gain sebesar 0,76 dengan criteria tingkat pencapaian tinggi. Aspek memahami bacaan mengalami peningkatan 85%, dan aspek menggunakan informasi dari bahan bacaan mengalami peningkatan70%. Hasil penelitian menyimpulkan bahwa terjadi peningkatan ability dan critical literacy siswa yang menggunakan bahan ajar berbasis literasi sains materi larutan penyangga.